Role of Rhizospheric Microbiota as a Bioremediation Tool for the Protection of Soil-Plant Systems from Microcystins Phytotoxicity and Mitigating Toxin-Related Health Risk - El Mahdi Redouane; Richard Mugani; Majida Lahrouni; José Carlos Martins; Soukaina El Amrani Zerrifi; Khalid Oufdou; Alexandre Campos; Vitor Vasconcelos; Brahim Oudra (Microorganisms, 2021)
Frequent toxic cyanoblooms in eutrophic freshwaters produce various cyanotoxins such as the monocyclic heptapeptides microcystins (MCs), known as deleterious compounds to plant growth and human health. Recently, MCs are a recurrent worldwide sanitary problem in irrigation waters and farmland soils due to their transfer and accumulation in the edible tissues of vegetable produce. In such cases, studies about the persistence and removal of MCs in soil are scarce and not fully investigated. In this study, we carried out a greenhouse trial on two crop species: faba bean (Vicia faba var. Alfia 321) and common wheat (Triticum aestivum var. Achtar) that were grown in sterile (microorganism-free soil) and non-sterile (microorganism-rich soil) soils and subjected to MC-induced stress at 100 µg equivalent MC-LR L−1. The experimentation aimed to assess the prominent role of native rhizospheric microbiota in mitigating the phytotoxic impact of MCs on plant growth and reducing their accumulation in both soils and plant tissues. Moreover, we attempted to evaluate the health risk related to the consumption of MC-polluted plants for humans and cattle by determining the estimated daily intake (EDI) and health risk quotient (RQ) of MCs in these plants. Biodegradation was liable to be the main removal pathway of the toxin in the soil; and therefore, bulk soil (unplanted soil), as well as rhizospheric soil (planted soil), were used in this experiment to evaluate the accumulation of MCs in the presence and absence of microorganisms (sterile and non-sterile soils). The data obtained in this study showed that MCs had no significant effects on growth indicators of faba bean and common wheat plants in non-sterile soil as compared to the control group. In contrast, plants grown in sterile soil showed a significant decrease in growth parameters as compared to the control. These results suggest that MCs were highly bioavailable to the plants, resulting in severe growth impairments in the absence of native rhizospheric microbiota. Likewise, MCs were more accumulated in sterile soil and more bioconcentrated in root and shoot tissues of plants grown within when compared to non-sterile soil. Thereby, the EDI of MCs in plants grown in sterile soil was more beyond the tolerable daily intake recommended for both humans and cattle. The risk level was more pronounced in plants from the sterile soil than those from the non-sterile one. These findings suggest that microbial activity, eventually MC-biodegradation, is a crucial bioremediation tool to remove and prevent MCs from entering the agricultural food chain.